Maternal serum omentin-1 profile is similar in humans and in the rat animal model. Issue 1 (September 2015) - Garcés, María F.; Ruíz-Linares, Carlos E.; Vallejo, Sergio A.; Peralta, Jhon J.; Sanchez, Elizabeth; Ortiz-Rovira, Alexsandra; Curtidor, Yurani; Parra, Mario O.; Leal, Luis G.; Alzate, Juan P.; Acosta, Bernarda Jineth; Diéguez, Carlos; et al.
Highlights Serum profile of omentin-1 was studied during human and rat gestation. Omentin-1 was detected in human and rat placenta using immunohistochemistry. Omentin-1 changes were not significant throughout gestation in either species. Human omentin-1 serum levels have an inverse relationship with triglyceride levels.